Is there an association between frontal fibrosing alopecia and sunscreen actives? - Chabaesele, Kutlwano Antonette (Department of Medicine, 2022)
Background Frontal fibrosing alopecia (FFA) is a subtype of primary scarring alopecia. It is associated with progressive, lymphocytic inflammation of hair follicles and permanent replacement by fibrous tissue. Clinically FFA is characterized by a band-like recession of the frontal hairline which may be associated with eyebrow (+/- body hair) loss and facial hyperpigmentation (most significant in pigmented skin). Early reports of FFA were in a few postmenopausal women, however, there has been an exponential increase in published cases (which include young women and men) in the last decade. Even though the cause remains unknown, an environmental factor is suspected. Aim The main aim of the study was to investigate whether there is an association between FFA and sunscreen actives, and to compare this with a histologically similar condition (lichen planopilaris - LPP) and another which also affects the marginal scalp (Traction alopecia – TA). The objectives were to obtain archival pathology tissue collected in the last decade from scalp biopsies and to use high-end spectroscopy and microscopy to detect the presence of sunscreen actives. Secondly, to investigate the survival and metabolism of cultured skin cells after exposure to various sunscreen actives. Methods The presence of sunscreen actives in formalin fixed paraffin-embedded (FFPE) punch biopsies of 9 FFA, 11 LLP and 5 TA, were compared. Tissue sections (5 μM) were embedded on microscopy glass slides and analysed using a scanning electron microscope (SEM). Elemental analysis of the biopsies sections was carried out using the energy dispersive X-ray microanalysis/spectroscopy (EDS) function on the SEM. In addition, Fourier-Transformed Infrared (FTIR) spectroscopy, was used to identify chemical bonds within biopsies, to potentially expose their molecular detail. The results were analysed using multivariate analysis known as Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA). Secondly, immortalized human keratinocytes (HaCaTs) as well as fibroblasts derived from FFA site specific biopsies (normal scalp, active edge and scarred area) from 4 FFA patients were exposed to 5 common sunscreen actives viz: titanium dioxide, zinc oxide, octyl methoxycinnamate, benzophenone-4 and 2-ethylhexyl dimethyl PABA, over a 24 hrs period. Thereafter, cell counting kit-8 (CCK8) assay was used to measure the cytotoxicity effect of the 5 sunscreen actives on HaCaTs and primary fibroblasts. Further, the metabolic phenotype switch of treated cells was analysed using the real-time extracellular flux bioanalyser. Results SEM/EDS - various elements were detected in patients' biopsies, many seemed to be lower in FFA compared to LLP and TA samples such as potassium, promethium, terbium, thulium and tin. Bromine, chlorine and indium were unique to TA samples; lead was only found in 2 LPP samples and 3 elements (antimony, plutonium and arsenic) were only unique to FFA samples. Zinc was detected in more FFA (33%) than LPP (9%) and TA (0%) samples. FTIR – various compounds were found in the FFPE sections. Strontium titanate was a significant contributor to the spectra separating FFA from TA; and although present was not significant for separating LPP vs. FFA and LPP vs. TA. Strotium titanate is used as a diamond simulant and one of the compounds it is produced from is titanium dioxide. Its use in jewellery makes it highly possible for it to come into contact with human skin. Moreover, there was no significant data point separation between FFA and LPP (R2 =55%), however, the R2 for FFA vs. TA and LPP vs. TA were 92% and 93% respectively and this shows that there was a good separation of data points between two groups comparison. Three compounds strontium titanate, potassium phosphate tribasic which is used as a food additive and 1,2-Dichloroethylene which is used in cleaning applications of electronics and metals, were found to be significant contributors for the separation of data points between FFA vs. TA. Whereas, molybdenum iodide anhydrous (a compound used for research purposes in optical phenomena) and sodium metaperiodate (used in fluorescent labelling) were responsible for the separation between LPP vs. TA. CCK8 - The human keratinocyte cell line and FFA primary fibroblasts showed varying susceptibility to sunscreen actives, with zinc oxide being most cytotoxic. Real-time extracellular flux analysis - zinc oxide induced an aerobic phenotype switch only on keratinocytes. Titanium dioxide induced an energetic phenotype switch in both cell types, but increasingly more in fibroblasts from FFA active edge and scar samples. Chemical sunscreen actives showed negligible effect on the energy phenotype of both cell types. Conclusion: Consistent with current clinical understanding, this proof-of-concept study found no significant FTIR spectra separation between FFA and LPP. However, strotium titanate (with source as titanium dioxide) may be a contributor to FFA pathogenesis. More FFPE samples from FFA patients had traces of zinc than those from LPP and TA. Further, zinc oxide proved to be the most cytotoxic and titanium dioxide to exhibit significant bioenergetic changes compared to chemical sunscreen actives on mono-layer cells (from a keratinocyte cell line and patient derived fibroblasts). The effect of physical sunscreen actives (traditional and nano-particles) warrants further investigations on more complex (closer-to-real-life) 3D in vitro and ex vivo FFA tissue culture models. Furthermore, investigating a larger cohort could improve identification of the link between sunscreen products and the development of FFA